2015
DOI: 10.1002/2015gl064939
|View full text |Cite
|
Sign up to set email alerts
|

HCFC‐133a (CF3CH2Cl): OH rate coefficient, UV and infrared absorption spectra, and atmospheric implications

Abstract: HCFC‐133a (CF3CH2Cl), an ozone‐depleting substance, is primarily removed from the atmosphere by gas‐phase reaction with OH radicals and by UV photolysis. The rate coefficient, k, for the OH + HCFC‐133a reaction was measured between 233 and 379 K and is given by k(T) = (9.32 ± 0.8) × 10−13 exp(−(1296 ± 28)/T), where k(296 K) was measured to be (1.10 ± 0.02) × 10−14 (cm3 molecule−1 s−1) (2σ precision uncertainty). The HCFC‐133a UV absorption spectrum was measured between 184.95 and 240 nm at 213–323 K, and a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…A radiative efficiency of 0.15 W m −2 ppb −1 (with a 23% uncertainty based on a 5%–95% confidence interval) was recently computed for HCFC‐133a based on measurements of its absorption cross section [ Etminan et al , ]. In the same study, the Global Warming Potential (GWP) for a 100 years time horizon was computed as 340, in reasonable agreement with the study by McGillen et al [], in which a GWP of 380 was calculated.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…A radiative efficiency of 0.15 W m −2 ppb −1 (with a 23% uncertainty based on a 5%–95% confidence interval) was recently computed for HCFC‐133a based on measurements of its absorption cross section [ Etminan et al , ]. In the same study, the Global Warming Potential (GWP) for a 100 years time horizon was computed as 340, in reasonable agreement with the study by McGillen et al [], in which a GWP of 380 was calculated.…”
Section: Introductionsupporting
confidence: 71%
“…Its tropospheric sink is dominated by the reaction with the hydroxyl radical (OH) [ Sander et al , , and references therein]. Recent laboratory and modeling studies by McGillen et al [] revealed good agreement with these earlier studies and yielded a tropospheric lifetime of 4.65 years, which is also in good agreement with that proposed by Carpenter et al []. However, the recent study by McGillen et al [], which included new measurements of UV photolysis rates, yielded a stratospheric lifetime of 103 years and is in disagreement with those reported by Laube et al [] and Carpenter et al [].…”
Section: Introductionsupporting
confidence: 58%
“…b Rate coefficients taken from NASA evaluation unless noted otherwise. c Rate coefficient and metrics taken from McGillen et al (2015) with RE lifetime adjusted and a factor of +1.1 for stratospheric temperature correction applied. (Table 1) with rate coefficients recommended in Burkholder et al (2015).…”
Section: Stratmentioning
confidence: 99%
“…Presently, there is no simple means to determine stratospheric lifetimes without the use of atmospheric models. Here, we have estimated stratospheric OH loss lifetimes, τ OH Strat , following a methodology similar to that used in the WMO (2014) ozone assessment, where results from 2-D atmospheric model calculations are used to establish a correlation between tropospheric (McGillen et al, 2015) and the PNNL database (Sharpe et al, 2004) were used in the analysis. b Rate coefficients taken from NASA evaluation unless noted otherwise.…”
Section: Stratmentioning
confidence: 99%
“…In contrast, HCFC-133a strongly correlates with CFC-113a in the first 3 years ( Table 2). The tropospheric lifetime of HCFC-133a is 4-5 years (McGillen et al, 2015), and its mixing ratios have varied in recent years. They increased in 2012/2013 and decreased in 2014/2015 (Vollmer et al, 2015).…”
Section: Enhancement Above Background Mixing Ratiosmentioning
confidence: 99%